Doing theology from below, from below? Bonhoeffer, De Gruchy, South Africa - Westhuizen, Henco van der (2020)
To address the issue of doing theology from below in South Africa, I will question how Bonhoeffer’s learning to see things from below has been interpreted from below. I will ask how John de Gruchy, who edited the new English edition of Bonhoeffer’s final fragments, interpreted him from below. In this light I will reflect on doing theology from below in South Africa.